Scrutinizing the impact of essential lean methods on sustainable performance in Malaysian manufacturing firms - Zainal Abidin, Muhammad Harith; Leman, Zulkiflle; Mohd Yusof, Zainal Abidin; Ismail, Md Yusof (Penerbit UTM Press, 2022)
Despite the fact that Malaysian manufacturing firms have implemented lean manufacturing principles to reduce resource waste and focus on customer demand, they still lack statistically validated lean manufacturing models to guide themin enhancing thesustainabilityof theirbusinesses.This paper conducts empirical research of the multi-dimensionalityof essential Lean Manufacturing (LM) methods (i.e.,Total Productive Maintenance (TPM), Continuous Improvement (CI), and Just-In-Time (JIT)) and their association with sustainable performance (SP). 69 of 121 respondents’ usable surveys were collected from manufacturing sectors that are recognised by the Negeri Sembilan Investment Centre (NSIC). They are made up of small, medium, and largebusinesses. The structural relationship of constructs was validated using the Structural Equation Modelling (SEM). For direct linkages between LM Methods with Sustainable Performance, the JIT is the most significant determinant, and for the inter-relationship between LM Methods, the Continuous Improvement and TPM, both were significantly inter-connected, depend on one another. In terms of LM implementation, the developed model contributes to the well-being and comprehension of practitioners engaged in top management. Sustainable indicators haveto be prioritizedfor manufacturing organization decision makers to ensure that the LM implementation is compatible with the sustainability impact.